2015
DOI: 10.1007/s00592-014-0708-6
|View full text |Cite
|
Sign up to set email alerts
|

Atazanavir improves cardiometabolic measures but not vascular function in patients with long-standing type 1 diabetes mellitus

Abstract: Aims Vascular disease is the leading cause of morbidity and mortality in type 1 diabetes mellitus (T1DM). We previously demonstrated that patients with T1DM have impaired endothelial function, a forme fruste of atherosclerosis, as a result of increased oxidative stress. Bilirubin has emerged as a potent endogenous antioxidant with higher concentrations associated with lower rates of myocardial infarction and stroke. Methods We tested the hypothesis that increasing endogenous bilirubin using atazanavir would … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
7
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 55 publications
1
7
0
Order By: Relevance
“…Moreover, our data verify a lack of benefit on endothelial function associated with long-term therapy in older subjects [50]. The results confirm our prior experience with atazanavir in patients with type 1 diabetes [28]. The lack of change in endothelial function is surprising given that increases in bilirubin decreased oxidative stress.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Moreover, our data verify a lack of benefit on endothelial function associated with long-term therapy in older subjects [50]. The results confirm our prior experience with atazanavir in patients with type 1 diabetes [28]. The lack of change in endothelial function is surprising given that increases in bilirubin decreased oxidative stress.…”
Section: Discussionsupporting
confidence: 84%
“…However, the increase in bilirubin could also have beneficial effects, as bilirubin is a well-described potent endogenous antioxidant [26, 27]. Atazanavir, presumably through its increase in bilirubin, could improve the systemic atherosclerotic environment through improvements in lipid profile, inflammation, and oxidative stress[25, 2830]. In support of this hypothesis, treatment with atazanavir slowed-progression in carotid intima media thickness compared to treatments with darunavir (another protease inhibitor] and raltegravir (an integrase inhibitor)[31, 32].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the antiretroviral drug atazanavir can competitively inhibit uridine diphosphate glucuronosyltransferase 1A1, leading to an increase in unconjugated bilirubinemia 15. Several studies have shown atazanavir use can improve endothelial function and reduce lipid levels and blood pressure in HIV‐uninfected diabetic patients 16, 17. Among HIV‐positive individuals, atazanavir decreased markers of inflammation and slowed progression of carotid intimal‐medial thickness when compared with other antiretroviral treatment (ART), an effect that appears to be partially mediated by bilirubin 18, 19…”
mentioning
confidence: 99%
“…In patients with type 1 diabetes, the initiation of ATV decreased lipid parameters and increased total plasma antioxidant capacity from baseline; however, similar to the studies of HIV-infected patients analyzed in this review, it did not result in an improvement in endothelial function [12]. In an experimental double-blind, placebo-controlled crossover study of HIV-negative patients with type 2 diabetes, ATV was associated with a significant improvement in both plasma antioxidant capacity and endothelial function [13].…”
Section: Discussionmentioning
confidence: 67%